2021
DOI: 10.1111/josh.13013
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of State Farm to School Procurement Incentives on School Purchasing Decisions

Abstract: BACKGROUND The most recent Farm to School (FTS) Census reported that of the 42% of US schools that participate in FTS, 77% procure food locally. In 2019, Colorado joined many other states in passing legislation that provides per‐meal incentives for purchasing local foods. However, little is known about how these incentives impact procurement decisions of school Food Service Directors (FSDs), and purported benefits of FTS cannot accrue without additional local purchases by school FSDs. METHODS We constructed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Tradeoffs may result from the fact that locally grown and raised food may be more expensive than nonlocal items ( 12 ). Local supply chains may incur higher transaction costs due to decreased efficiency.…”
Section: Perspective Guided By Literaturementioning
confidence: 99%
“…Tradeoffs may result from the fact that locally grown and raised food may be more expensive than nonlocal items ( 12 ). Local supply chains may incur higher transaction costs due to decreased efficiency.…”
Section: Perspective Guided By Literaturementioning
confidence: 99%
“…Incentives and policies affecting local food procurement can be viewed as economic development strategies through import substitution and spillover effects that improve access for farmers to new markets aiding in their growth and viability (Becot et al, 2017). Research examining incentives on school purchasing decisions found that even an incentive of $0.05 per meal reimbursement can impact local purchasing decisions (Long et al, 2021), yet the impacts of many public initiatives remain ill-explored, often due to data insufficiency (Jablonski & Schmit, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…School gardens specifically are associated with improved engagement and academic achievement (Klemmer, Waliczek, and Zajicek 2005;Smith and Motsenbecker 2005;Berezowitz, Bontrager Yoder, and Schoeller 2015). On a community level, farm to school programs can positively impact the local economy (Tuck et al 2010;Kane et al 2011;Bauman and Thilmany McFadden 2017), lead to increased employment (Kluson, 2012;Pesch and Bhattacharyya 2014;Holland et al 2015;Roche et al 2016;Christensen, Jablonski, and O'Hara 2017) and provide revenue streams for individual farmers (Izumi, Wright, and Hamm 2010;Long et al 2021).…”
Section: Introductionmentioning
confidence: 99%